STRATEGI PENGELOLAAN LINGKUNGAN BELAJAR OUTDOOR DI PAUD - Lilis, Lilis; Aulia, Aulia; Rifda, Rifda; Saroh, Ummu; Musthofa, M Bahri (STKIP Persada Khatulistiwa Sintang, 2024)
This research aims to determine strategies related to the outdoor learning environment at Sri Lestari Kindergarten Surabaya. This research was conducted using a qualitative descriptive method and used data collection techniques such as observation, interviews and documentation. The results of this research include the strategies used by school principals and teachers in managing outdoor learning at Sri Lestari Kindergarten, namely the integrated learning strategy. Outdoor learning strategies can make children feel happy and really help their growth and development. With outdoor learning, children will benefit from the development of physical, cognitive, language, moral and social emotional aspects. Outdoor learning can also improve children's endurance, balance and body coordination. The various areas in the outdoor play environment which are surrounded by nature are natural so that children can observe the objects around them. Outdoor learning must have a large area so that The children were really interested and enjoyed taking part in these outdoor learning activities. Sri Lestari Kindergarten has activities that can support student activity in their growth and development.